2022
DOI: 10.3389/fimmu.2021.754138
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immune Dysregulation Correlates With Clinical Features of Early Non-Small Cell Lung Cancer

Abstract: BackgroundSystemic immune dysregulation correlates with cancer progression. However, the clinical implications of systemic immune dysregulation in early non-small cell lung cancer (NSCLC) remain unclear.MethodsUsing a panel of 9 markers to identify 12 parameters in the peripheral blood of 326 patients (34 in the discovery group and 292 in the validation group), we investigated systemic immune dysregulation in early NSCLC. Then, we analyzed the impact of surgery on the systemic immune state of these patients. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Advanced solid malignancies are associated with generalized systemic immunosuppression ( 1 ) that may predispose not only for tumor progression and spread, but also for the development of serious microbial and viral infections ( 2 4 ). Notably, however, the existence of cancer-related systemic immunosuppression, seemingly from a much earlier stage in the process of tumorigenesis than was previously believed, has recently been convincingly demonstrated both in murine models of experimental tumorigenesis ( 5 , 6 ) and in a number of clinical studies, mostly focused on dendritic cell (DC) dysfunction in various types of cancer ( 1 , 7 13 ). In the former context, the preclinical study reported by Allen et al ( 6 ) is particularly noteworthy.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced solid malignancies are associated with generalized systemic immunosuppression ( 1 ) that may predispose not only for tumor progression and spread, but also for the development of serious microbial and viral infections ( 2 4 ). Notably, however, the existence of cancer-related systemic immunosuppression, seemingly from a much earlier stage in the process of tumorigenesis than was previously believed, has recently been convincingly demonstrated both in murine models of experimental tumorigenesis ( 5 , 6 ) and in a number of clinical studies, mostly focused on dendritic cell (DC) dysfunction in various types of cancer ( 1 , 7 13 ). In the former context, the preclinical study reported by Allen et al ( 6 ) is particularly noteworthy.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic immune dysregulation and cytotoxic agents induced hematopoietic damage together leading to lower peripheral lymphocytes in cancer patients [ 35 ], and people assume that low peripheral lymphocyte counts positively correlate with fewer tumor-infiltrating immunocytes and predict poor responses / outcomes [ 36 ]. Wang et al reported that total lymphocyte count was higher in the ICB benefit group [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, we could find in general that the MC2 subtype was strongly associated with the shortest OS and the highest stage of ccRCC. This might be due to the immune dysregulation [22][23][24] resulting in the MC2 subtype being less abundant in immune features such as tumor-infiltrating immune cells levels, TME, immune checkpoint molecules, chemokine/chemokine receptor, IFN score, immune cytolytic activity (CYT) score, angiogenesis score. Moreover, the MC2 subtype would benefit from immunotherapy based on the TIDE algorithm.…”
Section: Discussionmentioning
confidence: 99%